A retrospective series of conditions and mortality associated with extreme hyperferritinaemia in adults. Issue 9 (31st May 2018) - Thorne, Iona; Stroud, Javier; Penn, Henry
Summary: Background: Serum ferritin is commonly used in the diagnosis of iron deficiency anaemia. However, extreme hyperferritinaemia suggests a significant illness, including the differential diagnosis of haemophagocytic lymphohistiocytosis (HLH), which is rare and associated with a high mortality, particularly if untreated. This series aims to identify the causes and associated mortality of severe hyperferritinaemia in patients seen at a teaching hospital in London, UK. Method: Demographic and medical data were collected for all patients over 18 years of age with extreme hyperferritinaemia (defined as serum ferritin levels of ≥4000 mcg/L). Conditions associated with hyperferritinaemia and in‐hospital mortality were identified from medical records, laboratory data and discharge and death notification. Results: One hundred and fifty‐five cases of extreme hyperferritinaemia in adults were identified. Associated conditions included iron overload (35%), malignancy (24%), infectious disease (21%) and hepatocellular disease (12%). Autoimmune disease and HLH resulted in significantly higher median peak ferritin levels compared with all cases (10 616 mcg/L, P  < .01 and 19 138 mcg/L, P  < .05, respectively). Patients with confirmed HLH had the highest median peak ferritin. Uncommon infections were identified in this series, and included such as dengue, syphilis, HIV and murine typhus. HLH had been confirmed in seven patients (5%). In five patients (3%) no clear cause for raised ferritin was identified. Overall mortality in the whole cohort was 14% (n = 22), but there was a very high mortality of 80% in the group where no cause was found for the hyperferritinaemia, and these patients were significantly more likely to die during the index admission ( P  < .01). Conclusion: Extreme hyperferritinaemia is associated with a broad differential diagnosis of significant medical conditions, including iron overload, infections, cancer and liver disease. Rare infectious causes were also identified, and this series reports a greater proportion of cases of HLH than has previously reported. Unexplained hyperferritinaemia was associated with significant mortality.